2009
DOI: 10.1111/j.1468-0408.2009.00477.x
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Research on Performance Measurement and Management in the Public Sector Accounting Literature: A Review and Assessment

Abstract: This paper reviews the evolution of institutional research on performance measurement and management (PMM) in the public sector accounting literature. An assessment of the progress of this research programme is offered in light of some key developments in the broader neo‐institutional sociology (NIS) literature, such as the growing recognition of the role of embedded agency, the need to bridge institutional and rational choice explanations of action and the extension of empirical research across different leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
288
0
16

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(308 citation statements)
references
References 83 publications
4
288
0
16
Order By: Relevance
“…In a similar vein, Sharma and Lawrence (2005, 2009) have found that new accounting criteria favoured by donor agencies negatively impacted the housing and telephone sector, in terms of a substantial rise in prices, a reduction in the supply of housing and deterioration of telephone services in rural areas. These studies cover an important, largely neglected niche in PSMA in EEs.…”
Section: Culture and Politicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar vein, Sharma and Lawrence (2005, 2009) have found that new accounting criteria favoured by donor agencies negatively impacted the housing and telephone sector, in terms of a substantial rise in prices, a reduction in the supply of housing and deterioration of telephone services in rural areas. These studies cover an important, largely neglected niche in PSMA in EEs.…”
Section: Culture and Politicsmentioning
confidence: 99%
“…More research is needed to understand structural impediments to the 'ideal' MA repertoire and how management accounting tools are implemented and used in practice. 14 In this respect, we support types of research that see the new accounting tools not as neutral technicalities but as devices for changing power balances between stakeholders, for example NPM-like reforms that make managers more powerful at the expense of the interests of clients and workers (Ashraf & Uddin, forthcoming; in this review, see research by Rahaman & Lawrence, 2001;Sharma & Lawrence, 2005, 2009.…”
Section: What Do We Need To Know? Reflections and Directions For Futumentioning
confidence: 99%
See 1 more Smart Citation
“…The first is contingency-based research, which starts from the view that performance management practices depend upon certain contextual circumstances, such as the complexity of processes or environmental uncertainty (see, for example, Cavalluzzo and Ittner, 2004;Van Dooren, 2005;Moynihan and Pandey, 2010;Speklé and Verbeeten, 2014;and Kroll, 2015, for a review on the link between managerial performance information use and organizational performance). The second one is neo-institutional sociology, which highlights how performance management practices have become taken for granted due to certain pressures, and how these practices contribute to habitual types of actions (see Modell, 2009, for a review). Without denying the importance of these theories, some other theories are suggested here because they potentially enable an understanding of how decision-making by politicians drives their accounting information use.…”
Section: The Way Forward For Researchmentioning
confidence: 99%
“…In recent years a significant issue in public sector management literature has been that of understanding why not seldom the New Public Financial Management -NPFM-reforms have led to unintended as well as unexpected consequences (Guthrie, 1998;Newberry, 2002;Christiaens and Rommel, 2008;Lapsley;2009) and to management changes which are rather formal than substantial (Olson, Guthrie and Humphrey, 1998;Ter Bogt and Van Helden, 2000). Among the various approach used to explain the difference between actual and expected effects of accounting innovations different studies (Burns and Scapens, 2000;Scapens, 1994;Panozzo, 2000;Caccia and Steccolini, 2006;Ter Bogt and Van Helden, 2000;Ter Bogt, 2008;Siti-Nabiha, Scapens, 2005;Modell, 2009;Seal, 1999 ) have used the institutional theory.…”
Section: Introductionmentioning
confidence: 99%